PENGARUH PENAMBAHAN EKSTRAK BUAH MENGKUDU KEDALAM PROBIOTIK RABAL (Morinda citrifolia L) YANG DIBERIKAN PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE SANGKURIANG (Clarias gariepinus) - Nabilah, Aziz; Firman; Martudi, Suharun (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Catfish production needs to continue to be increased even further, including using probiotics enriched with noni fruit extract (Morinda citrifolia L). The aim of this research was to determine the effect of adding noni fruit extract (Morinda citrifolia L) to the Rabal probiotic given in feed on the growth and survival of Sangkuriang catfish (Clarias gariepinus).  This research was carried out for 60 days starting from February to May 2024, located in Bentiring Permai, Sidodadi Village, Bengkulu City. The research used a Completely Randomized Design (CRD) with 5 treatments and 4 replications, namely;  P0  (Probiotics without Noni fruit extract), P1   (Rabal probiotics with 10% Noni fruit extract , P2   (Rabal probiotics with 20% Noni fruit extract), P3   (Rabal probiotics with 30% Noni fruit extract) and P4   (Rabal probiotics with 40% Noni fruit extract).  The test fish used were 11 fish/container with a length of 6-8 cm. The variables observed were absolute length, absolute weight, feed conversion, efficiency and survival of Sangkuriang catfish. The addition of noni fruit extract to the RABAL probiotic had a very significant effect on the growth in length and weight of the test fish as well as feed conversion and efficiency. The best growth of sangkuriang catfish was in treatment P2 (rabal probiotic with 20% noni fruit extract)  with a survival rate of 100 percent.